A Drowning Case Including Mother and Her Own Children’s Homicide Suicide - Karbeyaz, Kenan; Akkaya, Harun; Balcı, Yasemin (The Bulletin of Legal Medicine, 2015)
There are rare cases of homicide-suicide by drowning for both murderer and victim or victims. In this study, presenting the mother who committed suicide by throwing herself into water after murdering her two children by same method. The mother in this case, a women 25 years who had been married for six years. She killed her two children (one of them is 5-years-old and the other is six months old) by throwing them into water, and she also committed suicide by jumping into the water. The case of the mother who committed suicide by throwing herself into the water after murdering her two children by throwing them into water is a rare condition. The case is found worthy for discussion of the manner of deaths and the reasons leading the mother to suicide and murder her children.